2002
DOI: 10.1097/00004872-200201000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced spontaneous baroreceptor sensitivity in patients with renovascular hypertension

Abstract: Patients with renovascular hypertension showed reduced cardiac baroreceptor reflex sensitivity and increased noradrenergic activity, which to some extent was reversed 1 year following successful renal angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…9 -11 Importantly, examining the same patient with or without renal hypertension did not show any difference in total noradrenaline spillover. 9,11 Reports of noradrenaline turnover in 2K1C rabbits have found no change in turnover from a range of tissues suggesting that there is not a generalized change in sympathetic activity in this model. 12 Thus there is a paradox.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…9 -11 Importantly, examining the same patient with or without renal hypertension did not show any difference in total noradrenaline spillover. 9,11 Reports of noradrenaline turnover in 2K1C rabbits have found no change in turnover from a range of tissues suggesting that there is not a generalized change in sympathetic activity in this model. 12 Thus there is a paradox.…”
mentioning
confidence: 70%
“…Results from a "within-patient" study, before and 12 months after reversal of renovascular hypertension, showed no change in total noradrenaline spillover, suggesting that the hypertension did not elevate global sympathetic activity. 11 Thus our assumption that RSNA reflects sympathetic activity in other beds is reasonable, but we cannot be certain about this without direct recordings. Nevertheless, our studies and others do not support the view that the activity of the sympathetic nervous system in general is enhanced in renovascular hypertension.…”
Section: Head and Burke Sympathetic Responses In Hypertensive Rabbitsmentioning
confidence: 93%
“…97 The secondary pathophysiological effects process includes elevation of renin levels, diminished peripheral and renal angiotensin II receptor response, 102 increased sympathetic tone, 103 and reduced baroreceptor sensitivity. 104 Elevation of renal vein renin is characteristic of renovascular hypertension, but the negative predictive value is low because phase III renovascular hypertension is associated with low renin levels. 97 Embolization from the aorta may also play a role in the pathophysiology of end-stage renal disease and hypertension, although evidence is scarce.…”
Section: Regional Disease Statesmentioning
confidence: 99%
“…Oxidative stress in the brain was suggested to contribute to SNS activation in other hypertensive models, [37][38][39][40] and BRS was impaired in other hypertensive models. 41,42) Thus, it is possible that the results obtained in the present study might be common in hypertensive models. Further studies are needed to determine these issues.…”
Section: Discussionmentioning
confidence: 78%